THE EFFECT OF ARGUMENT DRIVEN INQUIRY (ADI) MODEL ON STUDENTS' ARGUMENTATION SKILLS IN SCIENCE LEARNING - Celina Tasyya Salsabila; Arief Muttaqiin; Rahmah Evita Putri (ISER (Indonesian Science Education Research), 2025)
This study aims to analyze the effectiveness of the Argument Driven Inquiry (ADI) learning model in improving students' argumentation skills in science learning. The method used is a systematic literature review (SLR) with reference to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The review process was carried out through four stages, namely identification, screening, eligibility determination, and inclusion, so that relevant articles were published in the range of 2018 to 2025. The results of the study show that the ADI model is consistently able to improve students' skills in building data-based arguments, evaluating peer arguments, and reflecting on conceptual understanding. Compared to conventional learning and regular inquiry models, ADI has proven to be more effective because it integrates scientific practice, collaboration, and critical thinking skills. A number of studies have also reported a significant increase in posttest results and are inclusive of students with different academic abilities. Thus, the ADI model can be used as an effective learning strategy in supporting the mastery of science concepts as well as the development of 21st-century competencies, including critical thinking, creativity, problem-solving, and communication.